Trust in a complex world: enriching community - Heckscher, Charles (Oxford University Press, 2015)
This title explores current conflicts and confusions of relations and identities, using both general theory and specific cases. It argues that we are at a catalysing moment in a long transition from a community in which the prime rule was tolerance, to one with a commitment to understanding; from one where it was considered wrong to argue about cultural differences, to one where such arguments are essential.